ANALISIS PENGARUH DANA PIHAK KETIGA, TINGKAT SUKU BUNGA KREDIT, DAN TINGKAT INFLASI TERHADAP PENYALURAN KREDIT - Siswati - (Universitas Slamet Riyadi, 2015)
Bank is one of the financial institution having a major role in the world economy in the middle of a financial institution as financial intermediary between surplus unit and the deficit unit. One of the efforts of bank is credit. And this amount of credit in the character of an institution such as bank intermediation the surplus unit and the deficit unit. The source of fund from public and this should be distributed to people in form of credits. The background of this research is to analyze the factors that affect credit bank disbursement, by looking at the internal factor firm covering of third party funds (DPK ), interest rate (SBK), and inflation rate external company as a factor. This research uses 10 bank are largest credits, with a period of 2011 – 2013. The data analysis technique used multiple linear regression that was processed using SPSS. The results of this research is the third party funds (DPK) have a positive effects and significant on bank credit, interest rate have a positive effects and not significant on bank credit, and inflation rate have a positive effects and not significant on bank credit. Keywords: Distribution of Credit, Third Party Funds, Interest Rate, Inflation Rate